2002
DOI: 10.1021/ja0267728
|View full text |Cite
|
Sign up to set email alerts
|

Large Substituent Effect on the Photochemical Rearrangement of 1,6-(N-Aryl)aza-[60]fulleroids to 1,2-(N-Arylaziridino)-[60]fullerenes

Abstract: Large substituent effects were observed in the rates and reaction mechanisms of the photochemical rearrangement of N-arylaza-[60]fulleroid 1 to N-arylaziridino-[60]fullerene 2, in which the difference of the rates between the fastest and the slowest (>2160-fold) was attained only by changing the aryl group from 1-naphthyl to 2-naphthyl. The decreasing order of the reaction rates in relation to the substituents was 1-naphthyl (1b) > 1-pyrenyl (1d) > phenyl (1a) > 2-naphthyl (1c). The reactions proceeded via tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The presence of an sp 3 -carbon signal at δ C 83.63 ppm unambiguously indicated the formation of 6,6-closed cycloadduct. Carbon nuclei in the N-phenyl substituent resonated at δ C 121.55, 124.37, 129.28, and 145.62 ppm, and the fullerene moiety gave rise to 16 signals in the region δ C 140-145 ppm, in full agreement with the data of [10,12].…”
supporting
confidence: 82%
“…The presence of an sp 3 -carbon signal at δ C 83.63 ppm unambiguously indicated the formation of 6,6-closed cycloadduct. Carbon nuclei in the N-phenyl substituent resonated at δ C 121.55, 124.37, 129.28, and 145.62 ppm, and the fullerene moiety gave rise to 16 signals in the region δ C 140-145 ppm, in full agreement with the data of [10,12].…”
supporting
confidence: 82%
“…Ouchi, Ito and co-workers also observed a large substituent effect on the photochemical rearrangement of N-aryl-aza [60]fulleroids. [25] In contrast to C 60 monofunctionalization of C 70 leads to mixtures of regioisomers due to lower symmetry and to differences in reactivity between the various double bonds. There are each four different [6,6] (IϪIV) and [5,6] ring fusions (VϪVIII) (Scheme 3).…”
Section: Thementioning
confidence: 99%
“…[10] However, very little is known about the reactions of fulleroids, probably because of the limited synthetic methods using unstable diazoalkanes as well as their thermal and photochemical lability. [11] We have noticed that fulleroids [12] are easily separated from other fullerene derivatives if polar substituents are introduced, and they behave as a reactive intermediates on account of the reactive bridgehead double bonds. [13,14] In our preliminary study, [14] we have also found that some fulleroids show highly regioselective Diels-Alder (DA) reaction with 2,3-dimethyl-1,3-butadiene compared with the nonregioselective reaction with cyclopentadiene.…”
Section: Introductionmentioning
confidence: 99%